The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2000
DOI: 10.1016/s0886-3350(00)00317-5
|View full text |Cite
|
Sign up to set email alerts
|

Astigmatism correction with a foldable toric intraocular lens in cataract patients

Abstract: Early postoperative and long-term follow-ups showed effective and stable correction of astigmatism after implantation of a foldable toric posterior chamber silicone IOL.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
118
1
13

Year Published

2009
2009
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 197 publications
(140 citation statements)
references
References 5 publications
4
118
1
13
Order By: Relevance
“…O nosso estudo mostrou que a média da rotação da LIO foi de 3,2º, onde 95% das LIOs tiveram rotação menor ou igual a 10º, o que se traduz em uma estabilidade rotacional muito boa se compararmos com estudos como o de Shimizu et al (9) ou Ruhswurm et al (16) , os quais obtiveram rotações de até 30º com suas médias girando em torno de 15º de rotação, em nosso trabalho a rotação máxima foi de 13º. Trabalhos mais modernos como o de Till et al (17) mostram que 11% dos pacientes apresentaram rotação da LIO de até 15º, contra 5% observado no presente estudo.…”
Section: Discussionunclassified
“…O nosso estudo mostrou que a média da rotação da LIO foi de 3,2º, onde 95% das LIOs tiveram rotação menor ou igual a 10º, o que se traduz em uma estabilidade rotacional muito boa se compararmos com estudos como o de Shimizu et al (9) ou Ruhswurm et al (16) , os quais obtiveram rotações de até 30º com suas médias girando em torno de 15º de rotação, em nosso trabalho a rotação máxima foi de 13º. Trabalhos mais modernos como o de Till et al (17) mostram que 11% dos pacientes apresentaram rotação da LIO de até 15º, contra 5% observado no presente estudo.…”
Section: Discussionunclassified
“…A similar incidence of rotation even in vitrectomized eyes may be attributable to modified L-shaped haptic design and adhesive properties of the AcrySof toric IOL. 8,14 Another reason could be no tamponade during vitrectomy.…”
Section: Complicationsmentioning
confidence: 99%
“…Several studies mentioned various toric IOLs and found this method effective in correcting astigmatism. [8][9][10] Plate haptic and loop haptic toric IOLs have been used for about a decade, but are associated with postoperative rotational instability. 11 Recently, AcrySof toric IOL (Alcon Laboratories, Inc., Fort Worth, TX, USA) had good rotational stability and favorable efficacy in patients with cataracts and corneal astigmatism.…”
Section: Introductionmentioning
confidence: 99%
“…(Alio, Agdeppa et al 2010) Furthermore, based on a vector analysis of the refractive outcomes, the Acri.Comfort IOL has been shown to correct 91% of pre-existing astigmatism. (Alio, Agdeppa et al 2010) (Ruhswurm, Scholz et al 2000;Leyland, Zinicola et al 2001;Till, Yoder et al 2002) www.intechopen.com N = number of eyes; FU = follow-up; SD = standard deviation; D = dioptres; ° = degrees; % = percentage; UDVA = uncorrected distance visual acuity; BDVA = best-corrected distance visual acuity; VPI = visual potential index; RCT = randomised controlled trial; PCS = prospective cohort study; RS = retrospective study; * = converted from LogMAR to Snellen; ^= obtained by wavefront abberometry Table 2. Literature on monofocal toric IOLs (%) www.intechopen.com…”
Section: Refractive Outcomesmentioning
confidence: 99%